Parental Wealth and Children's Cognitive Ability, Mental, and Physical Health: Evidence From the UK Millennium Cohort Study - Vanessa Moulton; Alissa Goodman; Bilal Nasim; George B. Ploubidis; Ludovica Gambaro (Child Development, 2021)
This article investigates the influence of wealth, a frequently neglected aspect of the economic circumstances of families, on children's development. Using the UK Millennium Cohort Study, it explores whether parental wealth (net total wealth, net housing wealth, net financial wealth, and house value) is associated with children's cognitive ability, mental, and physical health at age 11 (N~=~8,645), over and above parental socioeconomic status and economic resources, in particular permanent income. Housing wealth was associated with fewer emotional and behavioral problems, independent of the full set of controls. Children's verbal cognition and general health were more strongly associated with family permanent income and socioeconomic characteristics than with wealth.
Additional information: Open access funding enabled and organized by Projekt DEAL.
Keywords: 330